Demography of Ocular Trauma in Pediatrics Patient, A Systematic Review - Nadia D. Quartantri (Jurnal KESANS : Kesehatan dan Sains, 2022)
Background : Ocular injuries are the most common cause of acquired monocular blindness in children. Eye injuries in childhood are largely preventable but unfortunately remain common. Objectives : We sought to perform a systematics review of demography ocular trauma in children over the past fifth years. Methods: A systematic review was performed on PubMed and Scopus search term “Pediatrics” “Trauma” and “Ocular”. Results: Four articles identified between 2017 and 2021 specifically addressed ocular trauma in pediatrics. A total of 1039 patients were included in these four studies. The incidence of close globe injury is higher than open globe injury, two journals claim that the most incidence of ocular trauma occurs in the home, the two others claim that outside/street is the most commonplace, the incidence in the male group is higher than female and incidence ocular trauma mostly occur in 2-14 years old age group. Conclusion: Overall, the average close globe injury incidence is 65,8% and the average of open globe injury is 22,4%. The most common injury that occurs in pediatric trauma is close globe injury.